2020
DOI: 10.1016/j.cmet.2020.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Enhances Autophagy and Normalizes Mitochondrial Function to Alleviate Aging-Associated Inflammation

Abstract: Highlights d CD4 + T cells from healthy older people preferentially produce a Th17 profile d Autophagy, but not mitophagy, knockdown activates a Th17 profile in ''young'' cells d Mitochondrial ROS is needed, but not sufficient, for a Th17 profile in ''young'' cells d Metformin improves autophagy and mitochondria in parallel to decrease inflammaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
255
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(305 citation statements)
references
References 91 publications
9
255
3
2
Order By: Relevance
“…Systemic inflammation is similarly associated with aging – often referred to as ‘inflammaging’ ( López-Otín et al, 2013 ), and this contributes to aging-related decline, as evidenced for example by the observation that inhibition of pro-inflammatory NF-κB signaling can reduce aging phenotypes ( Tilstra et al, 2012 ). Interestingly, recent research demonstrated that T cells may contribute to age-related inflammation and its metabolic complications, such as hyperglycemia ( Bharath et al, 2020 ; Desdín-Micó et al, 2020 ; Lee et al, 2019 ), and engineered T cells can prevent pathology by clearing senescent cells ( Amor et al, 2020 ). However, here we will focus on the inverse relationship: how do systemic changes associated with aging impact T cell responses, particularly in the context of cancer?…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation is similarly associated with aging – often referred to as ‘inflammaging’ ( López-Otín et al, 2013 ), and this contributes to aging-related decline, as evidenced for example by the observation that inhibition of pro-inflammatory NF-κB signaling can reduce aging phenotypes ( Tilstra et al, 2012 ). Interestingly, recent research demonstrated that T cells may contribute to age-related inflammation and its metabolic complications, such as hyperglycemia ( Bharath et al, 2020 ; Desdín-Micó et al, 2020 ; Lee et al, 2019 ), and engineered T cells can prevent pathology by clearing senescent cells ( Amor et al, 2020 ). However, here we will focus on the inverse relationship: how do systemic changes associated with aging impact T cell responses, particularly in the context of cancer?…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear the potential mechanism of preadmission metformin usage associated with lower mortality in AKI patients with diabetes. Metformin could improve autophagy and mitochondrial function in diabetes [26]and decrease in ammation by down-regulate proin ammatory cytokines, such as IL-6 and TNF-α [27,28]. Besides, metformin may have a potential role in antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Research linking the role of autophagy's impact on cellular and organismal lifespan as well as cellular nutrient and stress-sensing pathways has burgeoned in the last decade. This research has identified a growing list of pharmacological agents as well as diet and dietary compounds that lead to increased autophagy function and clearance of excess cellular protein [156][157][158][159][160][161][162][163][164][165][166][167].…”
Section: Manipulating For Lamina Protein Clearancementioning
confidence: 99%
“…Furthermore, activation of SIRT1 results in deacetylation of nuclear LC3, enabling relocalization of LC3 to the cytoplasm from the nucleus and promoting autophagy and potentially formation of nucleophagy-associated vesicles. Although there is debate surrounding target specificity of many compounds that target nutrient/energy sensing pathways, there is strong evidence linking increased AMPK and SIRT1 function with compounds such as metformin [158,159,162,[175][176][177] and resveratrol [160,[178][179][180][181][182][183], respectively to increased health and lifespan. The benefits of these compounds is likely through increased autophagy and indicates the potential therapeutic use of these compounds (or similar molecules with higher target specificity) to promote protein accumulation clearance from the lamina.…”
Section: Manipulating For Lamina Protein Clearancementioning
confidence: 99%